Self-professed Proficiency of Philippine Higher Education (PHE) Teachers of STEAM Disciplines. - Morales, Marie Paz E.
This study determined the self-professed proficiency of Philippine higher education (PHE) teachers of science, technology, engineering, agri/fisheries, and mathematics (STEAM) disciplines. Through the lens of technological pedagogical content knowledge (TPACK) framework and the standards of teaching the disciplines in STEAM in advance and higher learning as spelled out in the indicators of proficiency used in this research, the study informed the status of teacher quality in the different disciplines of STEAM. Sampled (Tier 1: stratified random sampling for 156 schools; Tier 2: complete enumeration) 1940 teachers (representing the different STEAM disciplines) took the online survey in January?December 2018. Selected teachers from the set provided interviews and classroom observations for data triangulation. Data analysis (i.e. programmed scoring framework, descriptive statistics, percentile rank, and t-test) determined that self-rated proficiency defined their competence. In terms of the aforementioned framework and standard, they perceived themselves as ?Highly Proficient to Distinguished? teachers. The qualitative data worked with these findings, but some coupled with student achievement (through licensure performance) revealed that teachers may have over-rated themselves. Males and females do not register significant differences in their perception of proficiency. School type (private and government-owned) do not index significant differences as well, except in Community Linkages and TPACK as a whole. These findings may inform policy creation to build a stronger Philippine Workforce 4.0. In fact, the tool (proficiency instrument) may be envisioned to initiate a highly structured micro-credentialing system of STEAM education in the country.